Pengaruh Strategi Pembelajaran Two Stay Two Stray (Ts-Ts) dan Snowball Throwing Terhadap Hasil Belajar Matematika Ditinjau dari Motivasi Belajar Siswa Kelas VIII Semester Ganjil SMP Negeri 1 Sawit Tahun 2016/2017 - Rahmawati, Riska, Drs. Slamet. HW, M.Pd (2016)
This research aims to understanding: (1) the effect of mathematics learning outcomes by using strategies of Two Stay Two Stray (TS-TS) and Snowball Throwing, (2) the effect of the mathematics learning outcomes viewed from students learning motivation,(3) the interaction between learning strategy and students' motivation toward mathematic learning outcomes. The type of the research is an experiment research with quasi-experimental design. The population ofthe research was all students of odd semester of class VIII of SMP N 1 Sawit in 2016/2017 academic year. Sample of this research consist of two classes. The sampling technique is taken by using cluster random sampling. Methods of data collection are taken by using documentation, questionnaire and test. Technique of data analysis by using analysis of variance withtwo different cell lines. The results of data analysis with significance level of 5% was obtined: (1) there is effect of Two Stay Two Stray (TS-TS) strategies and Snowball Throwing on the outcomes of students' mathematics learning with F_A= 4.424 (2) there is effect of learning motivation for the mathematics learning outcomes of students with F_B = 11.487, (3) there is no interaction between learning strategic and student learning motivation toward mathematics learning outcomes of students with F_AB= 0.018. Keyword: Mathematics Outcomes, Learning Motivation, Two Stay Two Stray (TS-TS), Snowball Throwing.